5 - Analyse de l’effet de la suréducation sur l’efficacité technique des entreprises au Cameroun - Njifen, Issofou (Africa Development, 2021)
Overeducation refers to the situation when an employee has a qualification above that which would currently be required for someone to get the job. Overeducated workers do not fully utilize the potential they have in their jobs. This under-utilization of skills raises questions about the ability of firms to maximise production. The objective of this article is to show that overeducation is a determinant of enterprises’ technical efficiency. Using data collected from a sample of enterprises in the services sector in Cameroon, the Data Envelopment Analysis Method and the estimation of a Tobit model are used to generate and identify respectively scores and factors of technical efficiency of these production units. The results show that the score efficiency is around 0,542 when scale returns are constant and 0,774 when scale returns are variables. Furthermore, the presence of overeducated employees in the firm, the inclusion of gender in the firm, the formal status and the entrepreneur’s characteristics are the major determinants of technical efficiency in Cameroon’s service sector.